Vida de Mina : guerrillero, liberal, insurgente / Manuel Ortuǫ Martínez ; prólogo de Manuel Lucena Giraldo - Lucena Giraldo, Manuel; Ortuǫ Martínez, Manuel (1927-) (Barlovento)
Bibliografía: p. 427-431. Índice